Multiculturalism: a panacea to the achievement gap in mathematics in public schools in Nigeria (2017)
Multiculturalism seeks to recognize, understand, and appreciate cultures other than one' own. Educational Researchers over the years have taken advantage of multiculturalism to bridge the achievement gap and inequality that are related to gender, exceptionality, race, class and ethnicity. Students' performance in Mathematics over the years shows that the teaching and learning of the subject has been consistently reported as poor in most of the secondary and primary schools in Nigeria. This poor performance is more profound in public school where the majority of students are enrolled in Nigeria. A critical look showed that the dearth of effective teaching and learning of Mathematics in public schools in Nigeria has been attributed to lack of resources. It is against these backdrops that this paper highlights the potentials of multiculturalism as a yardstick to bridge the achievement gaps in Mathematics teaching in public schools in Nigeria.